Jasa Hapus Akun dan Permasalahannya Ditinjau Dari Kekuatan Mengikat Perjanjian Antara Konsumen dengan Pelaku Bisnis Jasa Hapus Akun - Supeno Supeno; Fachruddin Razi; Putri Anelia Anmas (Universitas Batanghari Jambi, 2020)
Cybercrime is an unlawful act that utilizes computer technology based on the sophistication of the development of internet technology. With the development of the times, technology continues to innovate to meet all the needs desired by the community. The sophistication of this technology is often abused on irresponsible people for their own gain, the account delete service is present to prevent the cybercrime from occurring but there are still many problems judging by the binding power of the account delete service agreement. The purpose of this research is to expose the problem of the binding power of account delete services. from the results of the study shows that there are still many problems that occur in the services of deleting accounts especially the lack of binding power of agreements made by the parties in the transaction delete the account.